Long non‐coding RNA CCAT1 sponges miR‐490 to enhance cell proliferation and migration of non‐small cell lung cancer. Issue 3 (15th December 2020) - Wang, Jingluan; Sun, Nina; Han, Weizhong; Tong, Li; Xu, Tao; Li, Guo
Abstract : Background: Non‐small cell lung cancer (NSCLC) accounts for 85% of lung cancer which is the most frequently diagnosed malignancy in China. Colon cancer associated transcript 1 (CCAT1) acts as an oncogene in enhancing tumor progression. However, the effects of CCAT1 in NSCLC remain unclear. The purpose of this study was to explore the role of CCAT1 in NSCLC. Methods: Wound healing and transwell assays were performed to measure cell migration. RT‐qPCR was employed to calculate the mRNA level of CCAT1 and miR‐490. Results: High expression of CCAT1 was observed in NSCLC tissues and cells, with low expression of miR‐490. CCAT1 promoted the proliferation and metastasis of H1299 and A549 cells, while miR‐490 had the opposite effect. CCAT1 could specifically bind to miR‐490 and regulate its expression. MiR‐490 partially reversed the inhibitory effect of CCAT1 on cell proliferation and metastasis. Conclusions: The CCAT1/miR‐490 molecular axis has been shown to be important for the treatment of NSCLC. Abstract : CCAT1 promotes the survival and metastasis of H1299 cells, while miR‐490 has the opposite effect.The CCAT1/miR‐490 molecular axis has been shown to be important for the treatment of non‐small cell lung cancer.